Exploring Goal Commitment Predictors ff Boundary Role Persons (BRP) - Nurus Sa’adah; Fathul Himam; Achmad Sobirin (Integrated Journal of Business and Economics (IJBE), 2018)
As the face of the organization, BRPs were the target of representations and influence attempts by external agents. In effect, the BRPs were both the influencer and the recipient of influence from insiders and outsiders. This basic characteristic led potentially to higher levels of role conflict and tension for the BRPs than other organization members. Because of high risk and challenges, BRPs had to have goal commitment to maintain their loyalty. This study aimed to explore goal commitment predictors of BRPs. Data collection involved 162 colleges promotion officers in Yogyakarta and it was analysed through Partial Least Square (PLS). The results indicated that R-square on the goal commitment  was 0,398. The effect of conscientiousness on goal commitment was indicated by a correlation of 0,323 and t=4,245; the effect of communication climate on goal commitment was indicated by a correlation value of 0,206 and t=2,545; the effect of equity reward on goal commitment was indicated by a correlation value of 0,092 and t=1,534; the effect of opponent cooperation on goal commitment was indicated by a correlation value of 0,203 and t=2,915. The conclusion was communication climate, opponent cooperation, and conscientiousness influenced goal commitment significantly, but equity reward did not influence goal commitment significantly.